1995
DOI: 10.1210/jcem.80.3.7883824
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone mineral density after parathyroidectomy in primary hyperparathyroidism.

Abstract: Skeletal involvement in primary hyperparathyroidism is characterized by preferential loss of cortical bone, whereas cancellous bone is relatively spared. Little data are available concerning changes in bone density, particularly at sites containing more cancellous bone, after successful parathyroidectomy. Most patients with primary hyperparathyroidism are asymptomatic, but approximately 50% meet one or more criteria for surgery. In a prospective study of 34 patients who met one or more such criteria, bone dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
96
3
7

Year Published

1999
1999
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 16 publications
21
96
3
7
Order By: Relevance
“…The present study on Japanese patients showed that annual increments in both the cortical and cancellous bone mass after PTX were larger than those in any other study previously documented in Caucasian populations, as judged by the percentage recovery of radial or lumbar BMD values (11.6% and 12.2%, respectively) ( Figure 1). Moreover, although two studies have reported that the percentage increase in lumbar BMD after PTX was greater than that in radial BMD in Caucasian populations [16,17], our study showed that the extent of BMD increases at the two sites were not significantly different. These discrepancies might arise from racial difference, or might be because our patients suffered from more severe reduction in radial bone mass than their Caucasian counterparts did, as judged by comparison of background BMD parameters documented in the previous studies.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…The present study on Japanese patients showed that annual increments in both the cortical and cancellous bone mass after PTX were larger than those in any other study previously documented in Caucasian populations, as judged by the percentage recovery of radial or lumbar BMD values (11.6% and 12.2%, respectively) ( Figure 1). Moreover, although two studies have reported that the percentage increase in lumbar BMD after PTX was greater than that in radial BMD in Caucasian populations [16,17], our study showed that the extent of BMD increases at the two sites were not significantly different. These discrepancies might arise from racial difference, or might be because our patients suffered from more severe reduction in radial bone mass than their Caucasian counterparts did, as judged by comparison of background BMD parameters documented in the previous studies.…”
Section: Discussioncontrasting
confidence: 78%
“…These discrepancies might arise from racial difference, or might be because our patients suffered from more severe reduction in radial bone mass than their Caucasian counterparts did, as judged by comparison of background BMD parameters documented in the previous studies. The finding of a more pronounced increase in radial BMD values in a subset of patients with lower preoperative values at this site in several studies [14][15][16] would support the latter possibility. pHPT is a relatively common endocrine disease with few overt manifestations, presenting most often as asymptomatic hypercalcemia [1].…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations